Bartolomé Bennassar: un historiador entre Braudel y Labrousse - Alberto Marcos Martín (Les Cahiers de Framespa)
This article examines the first steps of Bartolomé Bennassar for historical research, those that would culminate in the completion of his doctoral thesis on Valladolid in the golden age and the so-called complementary thesis about the presence of the plague in northern Spain at the end of the 16th century. But above all, it analyzes the historiographic affiliation of both works, and in particular the debt contracted with authors such as Labrousse or Braudel, and examines in depth their content, to end up emphasizing their originality and highlighting the influence they have had on the subsequent development of Historical studies.